Does Firm Heterogeneity Impact the Effectiveness of Carbon Taxes? Experiments in Argentina and Mexico - Omar O. Chisari; Sebastián Miller (Inter-American Development Bank (IDB), 2014)
This paper examines the effectiveness of carbon taxes on macroeconomic performance when manufacturing firms have the opportunity to change their scale of operation and degree of formality. The hypothesis is that when tax evasion or elusion is possible, it cannot be ruled out that emissions increase rather than decrease due to the reallocation of resources from the rest of manufacturing towards informal small-scale firms. When informality is high, industry could adapt to carbon taxes by reducing the scale of operation of big firms and increasing the number of small firms. However, when taxes are enforceable in all types of firms, there is a cost in terms of GDP and employment, since small-scale firms are more labor intensive. For numerical experiments, two CGE models calibrated for Argentina and Mexico are used. The 'domestic leakage' is found to be more relevant for Argentina than for Mexico.
hdl:11319/6606
Keywords: Q54; C68; 330; Carbon taxes; Informality; CGE; Mexico; Argentina